Perbedaan Tekanan Darah Sebelum dan Sesudah Exercise Intradialysis Pada Pasien Hemodialisis di Unit Hemodialisis Rumah Sakit Panti Rahayu Gunung Kidul - Murni Yuliastuti, Christina; Pujiastuti, Th.Tatik; Suparmi, CB, Sr. Lucilla (STIKes Panti Rapih, 2021)
ABSTRACT Background:Hemodialysis defines as a process of cleaning the blood from waste substances through a filtering process outside the body. Patients with chronic renal failure undergoing hemodialysis often experience complications including hypotension. Several references state an alternative intervention to prevent complications of hypotension in hemodialysis patients with an Intradialytic exercise. Intradialytic exercise is a planned and gradual form of exercise that includes various stages of flexibility exercise, strengthening exercise and cardiovascular exercise performed during hemodialysis. Intradialytic exercise is aimed to improve the work of the heart, respiration and improve hemodialysis regulation for the better. Objective:This study was aimed to determine the difference in blood pressure before and after intradialytic exercise in patients undergoing hemodialysis. Methods:This research design used a quasi-experimental design with pre-test and post-test with control design. The samples were 38 respondents who taken by total sampling at the Hemodialysis Unit of Panti Rahayu Hospital. The samples were divided into the intervention group who undertook intradialytic exercise for 4 weeks, each respondent experiences twice a week, while the control group who did routine hemodialysis and independent exercise. Results:The results showed that the distribution of the characteristics of the respondents was 51-54 years old (18.41%) the sex was mostly male (63.2%) Most of them (55.3%) underwent hemodialysis for less than 2 years. Statistically, it was known that there was no significant difference in blood pressure before and after intradialytic exercise inside patient’s body of the control and intervention groups. There was no significant difference in blood pressure between the intervention group compared to the control group, but there was a dynamic difference in blood pressure in patients who did intradialytic exercise. Conclusion:There was dynamics of differences in blood pressure in patients undergoing intradialytic exercise, it is recommended that hemodialysis nurses at Panti Rahayu Hospital take care patients during hemodialysis so that these interventions are routinely carried out.